A SPECIALIST'S VIEW ON THE EPIDEMIOLOGICAL DESCRIPTION OF TORCH-GROUP INFECTIONS (REVIEW ARTICLE) - Siddiq Sh. Olimov; Gulnihol I. Sharipova (Central Asian Journal of Medicine, 2023)
The high comparative weight of TORCH-group infections affects both the demographic condition and the health of the mother and child. The most medically-socially significant specificity of TORCH-group infections is their destructive effect on all organs and systems of the fetus and, above all, its central nervous system, this effect increases the risk of miscarriage, stillbirth and the child's integrity, the formation of defects in its development and leading to disability. In this regard, among TORCH-group infections, toxoplasmosis, rubella, cytomegaly viral infection, as well as infections that call the simple herpes virus Type 1 and 2 are of particular epidemiological importance.